2022
DOI: 10.37394/232015.2022.18.63
|View full text |Cite
|
Sign up to set email alerts
|

Motivation Moderating the Influence of Organizational Culture and Leadership on Employment Performance

Abstract: This study aims to determine the test results of the influence of organizational culture and leadership on employee performance by using intervening variables derived from motivation. There are 87 respondents used in this study. All respondents are employees at the "ABC" university. This study uses a quantitative approach. The primary data used in this study came from the results of filling out the questionnaire. Partial Least Square analysis technique with SmartPLS program is used to analyze the data resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…The implementation of these leadership indicators will directly create a harmonious relationship between members, support and recognition felt by each individual which further has an impact on increasing loyalty, mutual trust and mutual cooperation of members in achieving organizational goals. In line with the research findings of Saluy et al (2022) found that leadership can improve performance and the implication is that organizational goals can be achieved.…”
Section: Discussionsupporting
confidence: 78%
“…The implementation of these leadership indicators will directly create a harmonious relationship between members, support and recognition felt by each individual which further has an impact on increasing loyalty, mutual trust and mutual cooperation of members in achieving organizational goals. In line with the research findings of Saluy et al (2022) found that leadership can improve performance and the implication is that organizational goals can be achieved.…”
Section: Discussionsupporting
confidence: 78%
“…The religious aspect reflected in the construction of humans who believe and fear God Almighty are independent, have a noble character, intelligent, skilled, and are physically and mentally healthy. These two aspects aim to produce ideal human beings who are physically, spiritually, and mental health and supported by intellectual, emotional, and spiritual intelligence (Alsa et al, 2021;Saluy et al, 2022).…”
Section: Philosophical Theorymentioning
confidence: 99%
“…People who are committed to their work will be able to handle and overcome these obstacles with the support of professional growth opportunities and quality training. Improving employee performance in the sequence requires strong organizational leadership (Riyanto, Endri, & Hamid, 2021;Saluy, Armansyah, Djamil, Mulyana, Pramudena, Rinda, & Endri, 2022). Future research may examine these characteristics: work pleasure, intention to stay, soft skill development, and on-and off-the-job training.…”
Section: Discussionmentioning
confidence: 99%